Safety and efficacy of pitolisant in children aged 6 years or older with narcolepsy with or without cataplexy: a double-blind, randomised, placebo-controlled trial. Issue 4 (April 2023) - Dauvilliers, Yves; Lecendreux, Michel; Lammers, Gert Jan; Franco, Patricia; Poluektov, Mikhail; Caussé, Christian; Lecomte, Isabelle; Lecomte, Jeanne Marie; Lehert, Philippe; Schwartz, Jean Charles; Plazzi, Giuseppe
Summary: Background: Narcolepsy is a life-long disorder characterised by excessive daytime sleepiness and cataplexy, often arising in childhood or adolescence. Pitolisant, a selective histamine H3 receptor inverse agonist, has been approved in Europe and USA for adults with narcolepsy with or without cataplexy, with a favourable safety profile. This phase 3 study aimed to assess the safety and efficacy of pitolisant in children with narcolepsy with or without cataplexy. Methods: For this double-blind, randomised, placebo-controlled, multisite study, we recruited patients aged 6–17 years with narcolepsy with or without cataplexy in 11 sleep centres in five countries (Italy, France, Netherlands, Russia, and Finland). Participants were required to have a Pediatric Daytime Sleepiness Scale score of 15 or greater and to have not received psychostimulants for at least 14 days before enrolment; participants who needed anticataplectics (including sodium oxybate) were required to have been on a stable dose for at least 1 month. Participants were randomly assigned to treatment with pitolisant or placebo in a 2:1 ratio at the end of screening. Randomisation was stratified by study centre and treatment was allocated using an interactive web response system. After a 4-week screening period including a 2-week baseline period, patients entered in a 4-week individual up-titration scheme from 5 mg a day to a maximum of 40 mg a day of pitolisant or placebo; treatment was administered at a stable dose for 4 weeks, followed by a 1-week placebo period. For the primary analysis, we assessed pitolisant versus placebo using change in the Ullanlinna Narcolepsy Scale (UNS) total score from baseline to the end of double-blind period in the full analysis set, defined as all randomly allocated patients who received at least one dose of treatment and who had at least one baseline UNS value. A decrease in the UNS total score reflects a reduction in both excessive daytime sleepiness and cataplexy. All adverse events were assessed in the safety population, defined as all participants who took at least one dose of study medication. An open-label follow-up is ongoing. This study is registered at ClinicalTrials.gov, NCT02611687. Findings: Between June 6, 2016, and April 3, 2021, we screened 115 participants and 110 were randomly assigned (mean age 12·9 [SD 3·0] years, 61 [55%] male, and 90 [82%] with cataplexy; 72 assigned to pitolisant and 38 to placebo); 107 (70 receiving pitolisant and 37 receiving placebo) completed the double-blind period. The mean adjusted difference in UNS total score from baseline to the end of the double-blind period was –6·3 (SE 1·1) in the pitolisant group and –2·6 (1·4) in the placebo group (least squares mean difference –3·7; 95% CI –6·4 to –1·0, p=0·007). Treatment-emergent adverse events were reported in 22 (31%) of 72 patients in the pitolisant group and 13 (34%) of 38 patients in the placebo group. The most frequently reported adverse events (affecting ≥5% of patients) in either group were headache (14 [19%] in the pitolisant group and three [8%] in the placebo group) and insomnia (five [7%] in the pitolisant group and one [3%] in the placebo group). Interpretation: Pitolisant treatment resulted in an improvement in narcolepsy symptoms in children, although the UNS was not validated for use in children with narcolepsy when our study began. The safety profile was similar to that reported in adults but further studies are needed to confirm long-term safety. Funding: Bioprojet.